Ultrasonic and Viscosity Studies of Poly ( Acrylic Acid ) Solutions - AL-Mayali, K. H.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Ultrasonic absorption, velocity, viscosity, adiabatic compressibility, relaxation time and relaxation amplitude measurements are reported on different concentrations of poly(acrylic acid) solutions in common solvent water using pulsed ultrasonic apparatus technique operating at 26 kHz and 30 ÂºC. Results show an increase of velocity, viscosity, and absorption coefficient ØŒrelaxation time and relaxation amplitude values with the increasing concentrations of the poly(acrylic acid) solutions, which might be the result of structural fluctuations of polymer molecules such as the segmental motions of the polymer chains. In contrast the compressibility decreases with the increasing concentration of this polymer. This study suggests there is an association between polymer and solvent molecules and also there is association between polymer molecules itself.